If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4 + -1x) = 2(5 + x) (4 * 3 + -1x * 3) = 2(5 + x) (12 + -3x) = 2(5 + x) 12 + -3x = (5 * 2 + x * 2) 12 + -3x = (10 + 2x) Solving 12 + -3x = 10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + -3x + -2x = 10 + 2x + -2x Combine like terms: -3x + -2x = -5x 12 + -5x = 10 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + -5x = 10 + 0 12 + -5x = 10 Add '-12' to each side of the equation. 12 + -12 + -5x = 10 + -12 Combine like terms: 12 + -12 = 0 0 + -5x = 10 + -12 -5x = 10 + -12 Combine like terms: 10 + -12 = -2 -5x = -2 Divide each side by '-5'. x = 0.4 Simplifying x = 0.4
| q=4*4.18*16 | | 4y=1.4y | | w^2+w-182=0 | | -0.3x+9.13=0.1x+9.53 | | 3-2y=3y-5 | | 2x^2-18/6x-18 | | 3(2)+3=9 | | X-7=3.23 | | 8x+9=2(4x+7)-5 | | 8x-9=2(4x+7)-5 | | 8x+14=2(4x+7)-5 | | 8x-14=2(4x+7)-5 | | 18x-7=2(4x+7)-5 | | 16x-7=2(4x+7)-5 | | n^2-6n-31=129 | | 2y+7cy=4 | | 6x-12/3= | | 8x-7=2(4x+7)-5 | | 8x-7=13(2x+7)-5 | | 4/92.66 | | 8x-71=2(2x+7)-5 | | 2m+5n+8m+6n= | | 8x-7=2(2x+7)-23 | | 4x+14-10x=16+2x-14 | | 3x^2+5y^2-6x-12=0 | | 8x-7=2(2x+7)-21 | | 8x-7=2(3.14x+7)-5 | | 8x-7=2(14x+7)-5 | | 4+16-2=2b-2 | | s^2+4s+1=0 | | 8x-7=2(13x+7)-5 | | 3x^2+3x-5+k=0 |